The Measurement Of The Effectiveness Level Of Zakat Distribution a Comparison Between The Zakat Colection Center in Malaysia and the national Amil Zakat agency (BAZNAS) in Indonesia - Efri Syamsul Bahri; Mohd Mizan Mohammad Aslam; Abdullah Mubarok; Suyadi Murdi Wiharjo; Hendro Wibowo (UIN Mataram, 2023)
In Malaysia, the Zakat Collection Center (PPZ) plays a role in collecting zakat in three Federal Territory areas: the Kuala Lumpur Federal Territory, the Labuan Federal Territory, and the Putrajaya Federal Territory. Meanwhile, the distribution of zakat is carried out by Baitulmal. Furthermore, in Indonesia, the collection and disbursement of zakat are carried out by the National Zakat Agency (BAZNAS). This study aims to compare the level of effectiveness of zakat disbursement between PPZ and BAZNAS. This study uses a quantitative method with the Allocation to Collection Ratio formula approach. The data is sourced from the summary of PPZ zakat reports and BAZNAS financial reports. Data were obtained from each entity's website for 2019-2021. The results showed that the level of effectiveness of the disbursement of PPZ zakat was 92%, and BAZNAS was 94%. It shows that the effectiveness of zakat disbursement on PPZ and BAZNAS is in the Highly Effective category. Zakat management entities worldwide need to respond to the results of this research to continuously optimize the effectiveness of zakat disbursement in the Highly Effective category. Thus, the benefit of zakat is genuinely felt by Mustahik